ENHANCING THE METHODOLOGY FOR DEVELOPING PROFESSIONAL AND ETHICAL COMPETENCE OF PRIMARY SCHOOL TEACHERS (Web of Teachers: Inderscience Research, 2026)
This article explores the development of professional and ethical competence among primary school teachers and methods to improve these competencies effectively. The study combines theoretical analysis of pedagogical literature with experimental investigation in educational settings, aiming to provide practical strategies for teacher development. The results demonstrate that structured professional training, reflective practices, and continuous mentorship significantly enhance teachers’ ability to incorporate ethical principles into their daily pedagogical activities. The findings highlight the importance of systematic methodology in fostering holistic professional and moral growth among educators, offering recommendations for policy implementation and educational practice.